THE IMPACT OF CORPORATE GOVERNANCE AND BOARD CHARACTERISTICS TOWARD FIRM VALUE OF BUMN COMPANIES - Audrey, Angela; Lukman, Hendro; Sriwati , Sriwati (International Journal of Application on Economics and Business, 2024)
Since 2014, there has been a massive increase in infrastructure development. The interesting thing about this industry is a decrease in the share price of these companies, especially state-owned companies that are mostly working on the infrastructure development. According to this phenomenon, a study was conducted to determine the effect of corporate governance and the characteristics of the board of directors on firm value which is a reflection of value of share in the market price. The characteristics of the board of directors consist of age, gender, tenure, and educational background. The audit committee, independent commissioners, and the board of commissioners are proxies for corporate governance. The data used are state-owned infrastructure companies listed on the Indonesia Stock Exchange from 2015-2022. The number of companies is 8 companies. The analysis uses multiple regression analysis, and they processed with Statistical Product and Service Solution (SPSS version 29). The results of this study indicate that the audit committee, age of directors, and educational background of directors have a significant effect on firm value. Meanwhile, the independent commissioners, board of commissioners, gender of directors, and tenure of directors do not affect firm value. The conclusion is that the role of the audit committee and the age and education of the board of directors play an important role in firm value. This study implies that the selection of the audit committee and the age and educational background of board members are the prominent focus of recruitment in a company to increase firm value.